Papers - Reclaiming Steel-foundry Sands (With Discussion) - A. H. Dierker (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1930)
Next to the metal itself, molding sand is the most important raw material used in the manufacture of steel castings. There are no accurate figures available but probably it would be safe to say that the average steel foundry uses approximately 1000 lb. of new molding sand per ton of castings produced. With untreated sands costing from two to four dollars (in some extreme cases it may run as high as eight or ten dollars) per ton delivered at the foundry siding, molding sand is an important item in the cost of making castings, and any information that may help to reduce this sand consumption should be of interest to the industry. Fundamental Considerations In a general way, molding sand in the average steel foundry passes through the cycle shown in Fig. 1. This diagram indicates that if all of the sand could be returned from the shakeout floor to the mixer no new sand would be required from the stock pile and molding costs would be reduced accordingly. Unfortunately, for reasons to be discussed later, it has heretofore been necessary to dilute the used sand constantly with new raw sand in order to maintain the properties that are essential to the production of satisfactory molds.